Model parametrization to access pineapple variety ‘’Smooth cayenne’’ nutrient status in Benin (West Africa) - Agbangba, Emile C.; Sossa, Elvire Line; Dagbenonbakin, Gustave D.; Diatta, Sekouna; Akpo, Léonard Elie (My University, 2011)
Nutritional diagnosis is an important tool for increasing fruit yield and fruit quality through efficient fertilization management. The aim of the study is to investigate whether there are specific DRIS norms for pineapple ‘Smooth Cayenne’ for a better soil fertility management in Benin. A preliminary Diagnosis and Recommendation Integrated System (DRIS) norms for ‘Smooth Cayenne’ pineapple growing in plantations of the township of Allada (Benin) are presented. DRIS norms were established from a data bank of leaf nutrient concentration (N, P, K, Ca, Mg, S and Zn) and fruit yield with 60 samples gathered from farmers’ plantations. The data were divided into high-yielding (>88 t/ha) and low-yielding (<88 t/ha) sub-populations and norms were computed using standard DRIS procedures. These norms were developed with data from only one cropping region, so they should be considered as preliminary, probably requiring some modification as more data become available. The norms were significantly different from those presented in the literature. We conclude that our results revealed that DRIS is not immune to bias from locality effects.
Keywords: soil fertility; Nutritional diagnosis; leaf nutrient concentration